PROBLEMS OF EARLY CHILDHOOD DEVELOPMENT IN THE ERA OF DISRUPTION - Nurul Zahriani Jf (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to analyze the problems of early childhood development in the era of disruption. The research method used is descriptive qualitative with a library study approach. The results of the study found that the use of technology in this era of disruption raises problems which affect the development of early childhood. This happens because of the lack of assistance, supervision, direction and knowledge from parents and teachers on technological developments and conditions in the learning process for early childhood. This study suggests that in an effort to face the era of disruption, parents and educators must be able to master technology and be more creative and innovative in providing better and more appropriate education, assistance, and control for the education and teaching process of children.Keywords: Development; problematic; the era of disruption